Microstructure and Properties in Metals and Alloys (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Microstructure design is key in targeting the desired material’s properties. Contributions related to microstructure design and characterization are collected in this Topic, together with their relation to the mechanical, fatigue, wear and corrosion resistance of different kinds of metals and alloys. The goal of this Topic is to present contributions related to the relationship between the microstructure and properties of metals and alloys for different applications, including aeronautical and aerospace applications. Different process routes are considered (thermo-mechanical routes and additive manufacturing) in this Topic. Contributions related to welding are also included.